Decision-Making Factors for Customers Choosing to Buy Green Products - Zainul Wasik; Suwandi S. Sangadji; Dedy Iswanto (Journal of Managerial Sciences and Studies, 2025)
Asian markets have been the focus of the current study on green consumer behaviour. Despite the literature's observations of Indonesian consumers' environmental concern, little is known about how they behave while buying environmentally responsible products. Thus, the goal of this research is to investigate the variables that affect Indonesian consumers' choices to buy eco-friendly products. This study tests a number of theoretically supported assumptions using a survey-based technique. 410 Indonesian workers in Surabaya were surveyed using a 38-item questionnaire and the snowball sampling approach. Both exploratory and confirmatory factor analysis were used to analyze the data. The suggested idea was tested using structural equation modelling. The results showed that respondents were enthusiastic about supporting environmental protection, aware of their responsibility towards the environment, and tended to seek and learn about environmentally friendly products. The study found that the following customers' decisions to buy eco-friendly items are influenced by the following factors: support for environmental conservation, desire to be environmentally responsible, experience using green products, green business friendliness, and social appeal. Marketers of green products might use these data to develop advertisements that emphasize the advantages of their products for the environment. These strategies will increase consumer satisfaction and have an impact on their purchase decisions. This study provides in-depth information on eco-friendly consumer behaviour in Indonesia by looking at the elements that affect customers' choices to buy environmentally friendly products.